FORMATION OF CREATIVITY AIMED AT THE PROCESS OF CREATIVE POTENTIAL COGNITION IN STUDENTS - Feruza Turdikhujaevna Exsonova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
creativeness: it is considered the ability of an individual to create new ideas that, in contrast to traditional thinking, serve to ensure the effectiveness of a certain behavior, activity or process, as well as to characterize his preparation for a positive solution to existing problems. The creative potential of an individual is reflected as its general characteristic. It is considered the initial condition and result of creative activity. This quality expresses the ability and readiness of the individual for self-expression. Moreover, on the basis of creative potential, the personal abilities, natural and social power of each individual are manifested in a holistic way.